PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT DALAM SISTEM AGROFORESTRY - Haryanto, Totok Dwinur (Universitas Slamet Riyadi, 2011)
Abstract : Cooperative forest management is a social forestry strategy to improve community prosperity. Cooperative forest management not only produce timber but also use all the forest resources. Forest management has been change not only for company profits, it’s also for advantages of local community inside and around the forest. Keywords : Forest Resources Management